The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1007/bf02523507
|View full text |Cite
|
Sign up to set email alerts
|

Solvent polarity influences product selectivity of lipase‐mediated esterification reactions in microaqueous media

Abstract: Esterification reactions were evaluated by using lipases fromRhizomucor miehei (Lipozyme IM20) andPseudomonas cepacia (PS‐30) with equimolar levels (1.77 mmol) of undecanoic acid and glycerol or 1,3‐propanediol (1,3‐PD) or 1,2‐propanediol (1,2‐PD) in organic solvents of log P (partition coefficient between 1‐octanol/water) values of (−0.33–4.5. Reaction yields (percentage of esterified undercanoate) with glycerol ranged from 1.4 to 72%, with greatest yields observed in solvents of log P 4.0–4.5 for Lipozyme, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…The choice of the solvent was based on solvent polarity, which was the main factor influencing the selectivity of lipase-catalyzed reaction [8]. Several research groups pointed out that solvent with Log P \ 2 could increase the specific production of monoacylglycerols [7]. On the other hand, solvent with Log P [ 2 was favorable for relatively high activity of enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the solvent was based on solvent polarity, which was the main factor influencing the selectivity of lipase-catalyzed reaction [8]. Several research groups pointed out that solvent with Log P \ 2 could increase the specific production of monoacylglycerols [7]. On the other hand, solvent with Log P [ 2 was favorable for relatively high activity of enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, solvent mixtures as reaction media have been employed in the selective enzyme-catalyzed reactions, and the advantages of using solvent mixtures versus other strategies have been discussed [5]. However, few studies applied systematically statistical methods to investigate the effect of solvent mixtures on the selectivity in enzyme-catalyzed reactions [6,7]. Response surface methodology (RSM) is a popular and effective statistical technique for the investigation of complex process.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acyl specificity has been related to structural features of lipases [54][55][56] and the chain length substrate selectivity of various lipases has been studied in a few works [57][58][59][60], including transesterification of methyl esters of C8 to C18 fatty acids [61]. Fatty acyl specificity has been related to structural features of lipases [54][55][56] and the chain length substrate selectivity of various lipases has been studied in a few works [57][58][59][60], including transesterification of methyl esters of C8 to C18 fatty acids [61].…”
Section: Influence Of the Structure Of Reacting Speciesmentioning
confidence: 99%
“…Hence they drew a conclusion that protic solvents such as ethanol and water favored the formation of 1,3-propanediol from glycerol, meanwhile binary solvents containing a ACCEPTED MANUSCRIPT 5 protic component showed a synergetic solvent effect on the selective dehydroxylation of glycerol to 1,3-propanediol. Kuo et al [22] proved that the solvent polarity had an influence on the reaction product selectivity for esterification reactions, which could be partially explained on the basis of different solvation and extraction properties of solvents. Unfortunately, up to now, there is still no uniform conclusion in regard to solvent selection as well as its action mechanism that can be drawn to adapt to diverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In general, solvent can play an important role in determining the catalytic performance for many reactions [21][22][23]. Gong et al [21] found the use of water or ethanol as a solvent reached a selectivity to 1,3-propanediol of 25.7%, 23.0% respectively, which was obviously higher than that of 1,3-dimethyl-2-imidazolidinone (DMI) or sulfolane.…”
Section: Introductionmentioning
confidence: 99%